2013
DOI: 10.1080/0158037x.2013.783473
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the effectiveness of a classroom activity designed to teach the value of lifelong learning

Abstract: Many agree that educational systems should instill in students the value of lifelong learning (LLL), but few have suggested how to accomplish that or how to measure the effectiveness of those curricular initiatives. We developed a technique intended to strengthen students' beliefs about the value of LLL and piloted use of a recently developed scale to assess changes in commitment to LLL. Using a quasi-experimental procedure, we presented students with faculty members' career biographies describing their person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…When the literature is examined, it is revealed that there are numerous indicators that lifelong learning should adopt as a strategy. There are certain numbers of studies carried out regarding lifelong learning [3][4][5][6][7], especially among European countries. Studies regarding the topic have been increasing gradually in recent years in Turkey [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…When the literature is examined, it is revealed that there are numerous indicators that lifelong learning should adopt as a strategy. There are certain numbers of studies carried out regarding lifelong learning [3][4][5][6][7], especially among European countries. Studies regarding the topic have been increasing gradually in recent years in Turkey [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%